2019
DOI: 10.1371/journal.pone.0221485
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GenoType MTBDRplus for the detection of drug-resistant Mycobacterium tuberculosis on isolates from Karachi, Pakistan

Abstract: Objective To compare the diagnostic performance of the GenoType MRBDR plus assay with the gold standard phenotypic drug susceptibility testing in the detection of drug resistance among culture isolates obtained from patients in Karachi, Pakistan. Design Mycobacterium tuberculosis isolates were obtained from 96 consecutive tuberculosis patients found to have resistance to isoniazid from two health centers in Karachi (January-Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
(24 reference statements)
6
6
2
Order By: Relevance
“… 23 , 28 , 30 , 32 Moreover, in the current study, gene mutations attributed to low level INH R mainly caused by the mutations in the promoter region of inhA gene were also observed. Such mutations were more frequent in our study (43%, 3/7) than the 10–12% reported by other studies conducted in Ethiopia, 29 , 33 in Pakistan (17%), 34 and in Switzerland (23%). 35 Mutations in inh A gene not only causes resistance to INH but also to the structurally related drug ethionamide, which shares the same target.…”
Section: Discussioncontrasting
confidence: 63%
“… 23 , 28 , 30 , 32 Moreover, in the current study, gene mutations attributed to low level INH R mainly caused by the mutations in the promoter region of inhA gene were also observed. Such mutations were more frequent in our study (43%, 3/7) than the 10–12% reported by other studies conducted in Ethiopia, 29 , 33 in Pakistan (17%), 34 and in Switzerland (23%). 35 Mutations in inh A gene not only causes resistance to INH but also to the structurally related drug ethionamide, which shares the same target.…”
Section: Discussioncontrasting
confidence: 63%
“…We studied 4542 INH resistant isolates for molecular markers and mutations causing INH resistance were identified in 85.5% with frequency of katG, inhA and combined katG and inhA mutations in 72.7%, 9.9% and 2.8% respectively. Our findings are consistent with the published data [11,12,30] but with a lower proportion of combined katG and inhA mutations in our population [12,31]. INH resistance profiles when studied, stratified by RMP results, significant differences were reported between RrHr-TB (n = 4078) and RsHr-TB(n = 464) with regard to proportion of INH conferring mutation detected (87.1% vs 71.6%) and frequency of the mutations in inhA (7.6 vs 30.2%), katG (76.3 vs 41.2%) and combined inhA and katG (3.1% vs 0.2%).…”
Section: Plos Onesupporting
confidence: 94%
“…This could be further increased to 90.3% (186/206) if both the inhA promoter and oxyR-ahpC intergenic region mutations were involved. The sensitivity of this study was comparable to that reported from Pakistan (90.6%) [27] but much higher than that from China (80.25%) [28] which both used GenoType MTBDRplus. We speculated that the difference between this study and another study from China [28] may be attributed to that the mutation prevalence of oxyR-ahpC intergenic region were showed in 5-20% INH resistant M. tuberculosis in China [5,29,30], however, GenoType MTBDRplus did not include probes targeted in oxyR-ahpC intergenic region.…”
Section: Discussionsupporting
confidence: 81%